2024
DOI: 10.1038/s41564-023-01561-1
|View full text |Cite
|
Sign up to set email alerts
|

Brain glucose induces tolerance of Cryptococcus neoformans to amphotericin B during meningitis

Lei Chen,
Xiuyun Tian,
Lanyue Zhang
et al.

Abstract: In bacteria, antibiotic tolerance, the ability of a susceptible population to survive high doses of cidal drugs, has been shown to compromise therapeutic outcomes.In comparison, whether fungicide tolerance can be induced by host-derived factors during fungal diseases remains unproven. Here, through a systematic evaluation of metabolite-drug-fungal interactions in the leading fungal meningitis pathogen, Cryptococcus neoformans, we found that glucose, on which the brain depends for fuel, induces fungal tolerance… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Drug-related factors impacting drug delivery into human nail tissue include drug molecular size, surface charge, lipophilicity, and polarity [ 1 , 10 ]. Recent findings suggest that factors present in the natural environment or in situ behavior of the pathogens may influence the effectiveness of a drug differently compared with controlled laboratory conditions [ 11 , 12 ]. During onychomycosis treatment, the keratin matrix that composes the dorsal plate of the nail is considered an obstacle to nail plate penetration.…”
Section: Discussionmentioning
confidence: 99%
“…Drug-related factors impacting drug delivery into human nail tissue include drug molecular size, surface charge, lipophilicity, and polarity [ 1 , 10 ]. Recent findings suggest that factors present in the natural environment or in situ behavior of the pathogens may influence the effectiveness of a drug differently compared with controlled laboratory conditions [ 11 , 12 ]. During onychomycosis treatment, the keratin matrix that composes the dorsal plate of the nail is considered an obstacle to nail plate penetration.…”
Section: Discussionmentioning
confidence: 99%
“…By screening a library of 340 metabolites, the authors identified that C . neoformans tolerance to AmB increases in high-glucose media, as more cells survived AmB treatment in the presence of high glucose in vitro [ 18 ]. Similarly, AmB was more lethal against C .…”
Section: Antifungal Persistence In C Ne...mentioning
confidence: 99%
“…The mutant strain lacking the MIG1 gene showed significantly reduced fungal load after AmB treatment, in the brains of mice with cryptococcal meningitis, confirming that brain glucose induces tolerance against AmB in vivo as well. Interestingly, a combination of AmB + aureobasidin A (sphingolipid biosynthesis inhibitor) showed better outcomes than the currently recommended combination treatment AmB+ flucytosine, in infected mice [ 18 ]. Although more research is needed, these 2 studies are great examples of the promises that adjuvant therapy holds.…”
Section: Antifungal Persistence In C Ne...mentioning
confidence: 99%